Study on the formation mechanism of viscoplastic line deposition for predicting filament width - Yifeng Yao; Qiang Gao; Kaicheng Yu; Lizi Qi; Zexue Lin; Jingfeng Xu; Yinze Li; Peng Zhang; Min Zhu; Lihua Lu (Materials & Design)
Currently, all popular 3D printing inks exhibit Herschel-Bulkley (HB) fluid characteristics. However, the filament spreading, which reduces printing precision, decelerates the development of complex hydrogel models for engineered tissues or organs. In this study, a finite element model (FEM) is established to investigate the impact of processing and fluid parameters on the spreading of the HB inks. The non-dimensional numbers Re (ratio of inertia to viscosity) and Bo (ratio of gravity to surface tension) are used to analyze the influence of parameters on filament formation. When Re > 0.077 and Bo > 0.15, inertial and gravitational forces significantly alter the pressure gradient near the nozzle, thereby affecting the final spreading width of the filament. Additionally, when the spreading is dominated by surface tension, the ranges of rheological parameters of materials as well as the process parameters in 3D printing can be determined by Re and Bo. Under this parameter range, the error between predicted filament widths and that of the printed filament can be controlled to less than 6.7 %. The spreading of HB inks during printing is accurately predicted.